Implementation of Discipline Character and Student Responsibilities Through Hizbul Wathon Extra Curricular - Ari Endartiningsih; Sabar Narimo; Muhammad Ali (Walidem Institute and Publishing (WIP), 2023)
The character of discipline and responsibility is part of the values ​​of character education that can shape students' personalities towards a better direction. In its application, this can be done through extracurricular activities of Hizbul Wathon as instilling moral values ​​and habituation. The purpose of this study was to find out how the character of discipline and student responsibility is implemented through the Hizbul Wathon extracurriculars and to find out the obstacles faced in implementing the character of discipline and student responsibility through the Hizbul Wathon extracurriculars. This study uses qualitative research that focuses on field research and uses a phenomenological approach. Data collection was carried out through interviews, observation, and documentation. The results of the study found activities in form, discipline, and responsibility namely; 1) religious activities 2) flag ceremony activities 3) UN practice 4) playing games 5) rigging exercises. The character of student discipline is the process in the extracurricular Hizbul wathon by getting used to being on time for every activity and being responsible for carrying out activities properly. The obstacle faced was the influence of fellow friends joking with each other so that the practice time was delayed, the coaches did not master the material, and the implementation of extracurricular Hizbul wathon activities was not optimal.